Beliefs on Second Language Learning among Pre-service Teachers in a Public University in Malaysia - Baharum , Nurul Najwa; Ismail, Lilliati; Shauki, Nur Baiti Ismail (Journal of Digital Sociohumanities, 2024)
The purpose of this research was to identify the Teaching of English as a Second Language (TESL) pre-service teachers’ beliefs about second language (L2) learning, to determine whether there is a significant difference in beliefs among the TESL pre-service teachers of different years of study and how these beliefs were formed. These are important as the pre-service teachers’ beliefs would have a direct influence on their practices as a teacher in future. This research was conducted with a sample size of 113 respondents using a mixed method design. Data collection is using the Belief About Language Learning Inventory, often known as BALLI approach to ensure a comprehensive understanding of individuals' beliefs. In addition, data was gathered using semi-structured interviews thus, guaranteeing a more in-depth understanding of the participants' experiences and beliefs. Descriptive statistics showed that the highest mean score was recorded for the “motivation and expectations” dimensions. The ANOVA results showed statistically significant difference in the mean scores amongst the different years of study. Interview results indicated that beliefs were dominantly influenced by social support and exposure to the L2, and intrinsic and extrinsic motivation. Results of the study could inform course developers and lecturers as to which aspects of language learning and pedagogical knowledge need to be focused on in the pre-service teachers’ curriculum.